MEWUJUDKAN INTEGRATED FARMING SYSTEM PERKOTAAN DENGAN POC TURI SEBAGAI PENGINTEGRASI DI CIPINANG MELAYU JAKARTA TIMUR - Darwati Susilastuti; Aditiameri; Vivi Lusia (Jurnal Bakti Masyarakat Indonesia, 2022)
An integrated Farming System (IFS) is an environmentally friendly agriculture that combines agricultural, fishery, livestock, and other activities with the concept of zero waste. IFS is very suitable to be applied to urban agriculture, because, with the IFS concept, you will get a friendly business environment, and efficient, does not require a large area of land, provides ecological benefits, and can prosper the manager. Residents of RW 01 Cipinang Melayu, East Jakarta already have various urban agricultural cultivation activities on the land under the Becakayu Toll Road, including vegetable cultivation with a hydroponic system, catfish and tilapia cultivation, chicken farming, pigeons, horticulture cultivation and seasonal food crops, including: are turi plants as barrier plants (fences), as well as vegetable horticulture cultivation. However, these activities are still partial, unintegrated, and unproductive in infertile landfills. Problems with partners are identified as follows: (1). Not yet understood integrated agriculture (IFS); (2). The existence of local resources of turi and other plants that have not been utilized, either as fertilizer, feed supplements, and compost; (3). There has been no attempt to turn his business into a business that produces commercial products; and (4). There is no rejuvenation/preservation of local resources of turi plants and others. The result of the PKM is that participants understand the concept of integrated agriculture by compiling an IFS map for urban agriculture RW 01, Cipinang Melayu Village which is used as a guide in modeling integrated agriculture by utilizing local Turi resources (Sesbania grandiflora, L.) as an integrator. Utilization of local turi plant resources, both as liquid organic fertilizer and as feed supplements, as well as compost has significantly increased plant productivity by increasing the yield of mustard plants by 100 percent.